Ecological Sensitivity Atlas of the Argentine Continental Shelf - Rodriguez, E.; Vila, L. (The International Hydrographic Review, 2018)
The Argentine Petroleum Institute, together with the National Institute for Research and Development of Fisheries and the Navy Hydrographic Service, is producing an Ecological Sensitivity Atlas of the Argentine Continental Shelf. The aims of this project are to indicate ecologically sensitive areas, in order to provide valid guidelines to effectively control oil pollution incidents in those areas and, in general terms, to contribute to the preservation of the marine environment. Also to determine oil tankers’ navigation routes and areas to be avoided when navigating waters and to create a database to aid in risk management, in pilotage associated with control of incidents causing oil pollution.